Balanceability of a work-sharing line using floating workers and its comparison with floating work strategy. Issue 19 (2nd October 2021) - Jeong, In-Jae; Jeon, Sumin
Abstract : This study deals with a long-term design issue of dynamic line balancing (DLB) when work- sharing is allowed among stations. The work-sharing can be implemented by floating works or floating workers where a portion of tasks or workers is shifted to the succeeding station respectively. We suggest a mathematical model to minimise line cycle time in floating-worker environments. The line considered in this study is a 2-skill chaining line where each worker can help only the immediately downstream station. We suggest a closed form condition of balanceable floating-worker lines (FRL) in case of straight line configuration and U-shaped line configurations along with a comparison with floating-work lines (FKL). We could prove that the FRL is more efficient than the FKL as long as the floating line is balanceable. In case of a U-shaped line, we find that both the FKL and the FRL are always balanceable with the minimum cycle time, which is the total task time divided by the number of stations.